A Literature Review on Smart Apps Creator-Based Teacher Performance Management Model for Strengthening Supervision in Elementary Schools - Jamal, Alim Ikmal; Wahira, Wahira (International Journal of Administration and Education, 2025)
This study reviews a teacher performance management development model leveraging the Smart Apps Creator application to enhance supervision effectiveness in elementary schools. In the current digital era, school supervision must adapt to innovative technologies to ensure quality foundational learning. The Smart Apps Creator offers a platform for real-time feedback, improved communication between teachers and supervisors, and increased accountability. This model emphasizes collaborative engagement, comprehensive user training, and equitable access to digital resources. By digitizing performance appraisals, feedback systems, and professional development tools, the platform encourages continuous improvement in teaching quality. Nevertheless, challenges remain, including limited digital literacy among educators, inadequate infrastructure in under-resourced schools, and resistance to shifting from traditional supervision practices. To overcome these barriers, the study advocates for structured implementation supported by training, policy alignment, and inclusive planning. It also recommends a mixed-methods research design and longitudinal evaluation to measure the model's impact on both teacher development and student learning outcomes. Findings from this review are expected to guide policymakers, school leaders, and educational stakeholders in integrating technology into supervision strategies that are sustainable, inclusive, and adaptable to diverse school contexts.